From International Experience to Intercultural Competence: Indonesian EFL Teachers' Reflection - Ulil Fitriyah; Utami Widiati; Yazid Basthomi; Anik Nunuk Wulyani (JEELS (Journal of English Education and Linguistics Studies), 2024)
Current developments in English Language Teaching (ELT) have heightened the urgent need for intercultural competence as another essential skill in contemporary language education. Today’s EFL teachers are required to possess intercultural competencies to effectively assist students in raising their intercultural awareness. This study aims to examine teachers’ international experiences regarding the development of their intercultural competence, utilizing the developmental model of intercultural sensitivity (DMIS) proposed by Bennett (1986, 2017) as the framework. Through the application of a multiple narrative approach, we analyzed the stories of two higher education teachers, collected via document study and three-cycle interviews. The results demonstrate the complexities of teachers’ intercultural competence development and highlight an important aspect: one’s intercultural progression, as they may flexibly alter based on the situation and condition faced at a given moment.